Implementasi Model Self Directed Learning dalam Pembelajaran Menulis Teks Laporan Hasil Observasi Kelas VIII MTs N I Boyolali Program Khusus Tahun Aajaran 2025 - Puspasary, Al Qony Puspasary; Wicaksono, Andi (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to find out the planning, implementation, and writing skills of grade VIII students of MTs N 1 Boyolali special program. The research method used is qualitative descriptive with the type of case study research. The data collection techniques in this study were carried out by observation, interviews, and documentation. The validity of the data uses triangulation of source theory and method. The data analysis technique used is Miles and Huberman with the steps of data collection, data reduction, data presentation, and conclusion drawn. The results of the research and data analysis in this study. 1) The planning of Indonesian learning in learning to write the text of the observation report has been carried out by MTs N 1 Boyolali teachers together with MGMP Boyolali Regency, and has been in accordance with the rules of the independent curriculum, namely making teaching modules, ATP, CP, strategies, methods, materials, media and evaluation. 2) The implementation carried out has been in accordance with the initial planning which is summarized in three components, namely preliminary activities, core activities, and closing activities. In the core activities, teachers have used the SDL model of independent ability, which is to conduct questions and answers individually for students and combined with a project to write a text of the observation report that was previously asked to be observed in the school cooperative. 3) Assessment of writing skills of grade VIII students Special program using Youtube media has been in accordance with the plan. The assessment carried out is the structure including the title, opening, content, and closing. The linguistic aspect includes definition sentences, conjunction words and description sentences. The score obtained by students in grade VIII of special programs from groups 1-7 is an overall 80-90. This value has exceeded the KKTP set by the school.